The development and importance of tourism infrastructure in the aerotropolis: a case study - Kowalczyk, Andrzej; Gierczak-Korzeniowska, Beata (Rozwój i znaczenie infrastruktury turystycznej w aerotropolis – studium przypadku, 2019)
Tourism infrastructure is one of the main elements enabling the development of tourism and recreation. It also gives a specific location a competitive advantage, often resulting from urban processes in areas which, by definition, perform completely different socio-economic functions. This is the case with new urban structures, such as aerotropoli, generated as a result of the integrated planning and management of large airports and airport-related areas. The main purpose of the work is to present the process of the development of tourism infrastructure at the aerotropolis and emphasize the role of created investments for the entire area located around Hong Kong International Airport. The article describes the processes related to the development of tourism infrastructure within the aerotropolis on Lantau Island. Reference was made to several subsystems including, among others, Hong Kong International Airport, the town of Tung Chung (also called Tung Chung New Town), Hong Kong Disneyland Resort and Ngong Ping 360. The publication is descriptive and illustrative, and is based on an analysis of the literature on the subject and Internet resources. The described case confirms that the physiognomy of airports and airport-related areas in the urban structure undergoes significant changes. They are transformed from facilities serving almost exclusively to meet transport needs to multifunctional spaces, which see the vicinity of the airport as an opportunity for the development of tourism and specific forms of tourism
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 34-49
Keywords: aerotropolis; tourism infrastructure; Tung Chung New Town; space; Hong Kong Disneyland Resort; Ngong Ping 360; infrastruktura turystyczna; przestrzeń